Has Oppy Done Away with the Aristotelian Proof?. (13th July 2020) - McNabb, Tyler; DeVito, Michael
Abstract: In this essay, we engage with Graham Oppy's work on Thomas Aquinas's First Way. We argue that Oppy's objections shouldn't be seen as successful. In order to establish this thesis, we first analyze Oppy's exegesis of Aquinas's First Way, as well as the counter‐arguments he puts forth (including the charge that Aquinas's argument is invalid or, if deemed valid, forces one to adopt determinism). Next, we address Oppy's handling of the contemporary scholarship covering the First Way. Specifically, we lay out Edward Feser's most recent formulation of the argument and analyze Oppy's main objection to it.